KOMPOSISI DAN KELIMPAHAN LARVA DAN JUVENIL IKAN YANG BERASOSIASI DENGAN TINGKAT KERAPATAN LAMUN YANG BERBEDA DI PULAU PANJANG, JEPARA - WAHYU ADI (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2007)
Seagrass bed in Indonesia generally was the place sought a living, spawned, the enlargement and the protection for various kinds of the sea biota. The larva, as one of the biotas that make use of lamun, Was the development of the life of the fish that was begun from the egg as far as the mature form. The research about existence, of relations between abundance and fish larva and juvenile composition in seagrass bed and the density that was different often was not yet done, considering the importance of the fish larva for the fathoming of stock. This research aimed at knowing the fish larva kind and juvenile that associated with seagrass, as well as to know the composition and abundance of the larva and juvenile available in the Pulau Panjang, Jepara.